Relationship Between the Feeding Habits of Chlamys farreri and the Community Structure and Abundance of Phytoplankton in the Yellow Sea - Lei Li; Jiaying Cai; Dagui Liao; Yinjie Zheng; Wei Kang; Qian Gao; Xinya Chen; Yebing Yu; Yanming Sui; Mei Jiang (Fishes, 2025)
Filter-feeding shellfish primarily rely on suspended particles in the surrounding waters for nourishment. This study aims to understand the potential food sources for Chlamys farreri in the Yellow Sea off Long Island, Shandong Province, China, by comparing the phytoplankton composition in the aquaculture waters with the stomach contents of the scallops. The abundance of dominant species in the aquaculture waters exhibited significant shifts between summer and autumn. Key environmental factors influencing phytoplankton abundance included salinity and nutrient levels. Notably, there were differences in the types of phytoplankton that C. farreri could filter and consume, displaying a marked preference for 17 distinct phytoplankton species during foraging. The proportional similarity observed in summer suggested that C. farreri feeding behavior was selective and not influenced by the surrounding phytoplankton community. Diatom phytoplankton dominated both the aquaculture waters and the stomach contents of the scallops, while only minimal amounts of Dinoflagellates, Cyanophyceae, Chlorophyceae, and Chrysophyceae were found in the stomach contents. This relationship between marine phytoplankton and the stomach contents of the scallops provides foundational data for enhancing aquaculture yields of C. farreri.